GnRH and prostaglandin- based synchronization protocols as alternatives to progestogen- based treatments in sheep - Rekik, Mourad; Haile, Aynalem; Abebe, A.; Muluneh, D.; Goshme, Shenkute; Ben Salem, I.; Hilali, M. El-Dine; Lassoued, N.; Chanyalew, Y.; Rischkowsky, Barbara A. (Wiley, 2016)
The study investigated, for cycling sheep, synchronizing protocols simultaneously to the standard “P” protocol using progestogens priming with intravaginal devices and gonadotropin. In November 2014, 90 adult Menz ewes were assigned to either the “P” protocol, “PGF” treatment where oestrus and ovulation were synchronized using two injections of prostaglandin 11 days apart or a “GnRH” treatment where the ewes had their oestrus and ovulation synchronized with GnRH (day 0)–prostaglandin (day 6)–GnRH (day 9) sequence. The ewes were naturally mated at the induced oestrus and the following 36 days. Plasma progesterone revealed that 92% of the ewes were ovulating before synchronization and all, except one, ovulated in response to the applied treatments. All “P” ewes exhibited oestrus during the 96‐hr period after the end of the treatments in comparison with only 79.3% and 73.3% for “PGF” and “GnRH” ewes, respectively (p < .05). Onset and duration of oestrus were affected by the hormonal treatment (p < .05); “GnRH” ewes showed oestrus earliest and had the shortest oestrous duration. Lambing rate from mating at the induced oestrus was lower for “P” than for “PGF” ewes (55.6% and 79.3%, respectively; p < .05). The same trait was also lower for “P” than for “PGF” and “GnRH” ewes (70.4%, 89.7% and 86.7%, respectively; p < .05) following the 36‐day mating period. Prostaglandin and GnRH analogue‐based protocols are promising alternatives for both controlled natural mating and fixed insemination of Menz sheep after the rainy season when most animals are spontaneously cycling.